Strategi meningkatkan rasa percaya diri terhadap Lansia di daerah kota Padangsidimpuan - Nadira amalia tamima Nasution; Mia Aulina Lubis (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Self-confidence is a major problem for the elderly involving a negative self-evaluation. One strategy to increase self-confidence in the elderly is to hone the skills of the elderly so that the elderly can be more productive so that they help the elderly adjust to the surrounding environment and so that the elderly can adapt well due to the aging process so that the impact of decreased self-confidence does not develop into psychological disorders such as depression. The same thing also happened to one of the elderly who lived behind the Padangsidimpuan City Social Service who needed help to increase his self-confidence again. The process of providing assistance was also carried out in the PKL 1 mini project activity, using the case work method through the general intervention stage consisting of Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation and Termination. The purpose of honing skills for the elderly is to be able to increase self-confidence in the elderly